Evaluation of French Bean (Phaseolus vulgaris L.) Varieties for Summer Season Production in the Mid–Hills of Central Region of Nepal - Dhakal, Mira; Shrestha, Surendra Lal; Gautam, Ishwori Prasad; Pandey, Suprabha (Nepalese Horticulture, 2020)
The experiment on evaluation of open pollinated genotypes of French bean (Phaseolus vulgaris L) was conducted during the summer season of 2016 and 2017 at HRD, Khumaltar, Lalitpur, Nepal to assess the variability in the genotypes and yield potentiality for commercial production. The experiment was laid out in Randomized Complete Block Design (RCBD) with five replications. The two new genotypes viz. Semi Light Long and Long Green Bean were compared with Trishuli and Four Season. Fresh pod yield and yield attributing parameters were recorded. The pooled analysis of both years’ data showed significant differences among the genotypes on plant uniformity, number of pods/plants, single pod weight, fresh pod yield/plant and total yield. The number of pods per plant was observed the highest in Semi Light Long (113) followed by Long Green Bean (82) whereas the lowest in Trishuli (73). Similarly, the average pod weight was the highest (12 g) in Long Green Bean and the lowest in Trishuli (9.65 gm). The highest fresh pod yield per plant was observed in Semi Light Long (1188.5 g) followed by Long Green Bean (1015.00 g) and the lowest in Trishuli (768.50 g). The highest total pod yield was observed in Semi Light Long (30.97 t/ha) followed by Long Green Bean (27.02 t/ha) which were statistically at par. The lowest yield was observed in Four seasons (20.58 t/ha). Semi Light Long was also found to be early maturing (70-75 DAS), having long harvesting period (28 days) and thin flesh having pod length of 18-20 cm. Long Green Bean was late in maturity (75-78 DAS), second highest yielder (27.02 t/ha) with thick flesh and light green color at maturity. Based on the two years’ data, Semi Light Long and Long Green Bean genotypes seemed promising during summer season in the central mid hills of Nepal. So, it is suggested that these two genotypes may be considered for registration by the Seed Quality Control Center.